FOURS TRADITION AND UPDATES - G. Doshanova (Web of Journals Publishing, 2024)
This article analyzes the forms of poetry in the lyrics of one of the modern poets, Mahmud Toir, and issues of tradition, experience, and renewal in them.
Keywords: Cake, art form, poetics, tradition, experience, research.